Admission of medical patients from the emergency department: An assessment of the attitudes, perspectives and practices of internal medicine and emergency medicine trainees. (19th May 2016) - Lawrence, Sean; Sullivan, Clair; Patel, Nadia; Spencer, Lyndall; Sinnott, Michael; Eley, Rob
Abstract: Objective: We sought to obtain a deeper understanding of the differing needs and expectations of inpatient and ED medical staff regarding the admission process for medical patients. Design: Online questionnaire regarding their attitudes to and perceptions of various aspects of the admission process was used. Setting: The setting is a tertiary 640‐bed adult hospital with over 60 000 ED presentations per year and an inpatient admission rate of 30%. Results: A total of 42 out of 56 (75%) internal medical trainees (IMT) felt that the ED admission workup standard was lower or much lower than the inpatient standard; however, 10 of 16 (62.5%) ED trainees (EDT) thought it was similar ( P = 0.009). Regarding why IMT order additional tests in the ED, the major reason supported by IMT was to 'identify or exclude urgent pathology' (53/56, 96.4%); however, this reason ranked only fifth for EDT (2/16, 12.5%) who ranked 'to ensure nothing was missed' (12/15, 80%) first. A total of 24 out of 56 (42.8%) IMT felt that if ED admissions were enacted without IMT review, inappropriate admissions to hospital would occur regularly although only one of 16 EDT (6.3%) agreed ( P = 0.025). A total of 14 out of 16 (87.5%) EDT but only 16 of 56 (23.2%) IMT were comfortable with admissions occurring without inpatient review in the ED ( P < 0.001). The top two perceived barriers to a smooth and timely admission process for IMT were patient instability (34/43, 79.1%) and inadequate ED workup (37/49, 75.5%); for EDT, they were excessive IMT workload (11/14, 78.6%) and referral close to the end of an IMT shift (7/11, 63.6%). Conclusion: Substantial barriers to more harmonious admission processes exist. A 'paradigm shift' where roles and responsibilities are clear might be required. Defusing tension across the ED–inpatient interface should improve efficiency and ensure that patient outcomes remain the focus.